The antimicrobial action of low-molar-mass chitosan, chitosan derivatives and chitooligosaccharides on bifidobacteria - Simůnek, J; Koppová, I; Filip, L; Tishchenko, G; Bełzecki, G (Folia microbiologica, 2010)
The crude fractions of chitooligosaccharides (COS) and low-molar-mass chitosans (LMWC) were prepared by enzyme hydrolysis of chitosan (CS). Specific growth rate of B. adolescentis, B. bifidum, B. breve, B. catenulatum, B. infantis and B. longum ssp. longum was determined in the presence of 0.025 and 0.5 % COS (<5 kDa), LMWC (5-10 kDa), and 0.025, 0.1 and 0.5% of CS, chitosan succinate and chitosan glutamate in vitro. Minimum inhibitory concentrations (MIC; assayed by colony counting on TPY agar plates) of COS-LMWC and CS ranged from 0.025% to 0.75% of CS-LMWC. The growth of all bifidobacterial strains in the presence of chitosan, its derivatives and LMWC decreased at a concentration of 0.025%; the bacterial growth was completely inhibited at a concentration of 0.5%. COS did not show any inhibitory effect, an increased growth rate was even observed in the case of B. bifidum, B. catenulatum and B. infantis.
Keywords: Microbial Sensitivity Tests; oligosacharidy; Oligosaccharides; mikrobiální testy citlivosti; Chitosan; Bifidobacterium; Anti-Bacterial Agents; chitosan; antibakteriální látky; Colony Count, Microbial; počet mikrobiálních kolonií